Effects of range of motion on resistance training adaptations: A systematic review and meta-analysis - Pallarés, J. G.; Hernández-Belmonte, A.; Martínez-Cava, A.; Vetrovsky, T.; Steffl, M.; Courel-Ibanez, J. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Background: Nowadays, there is a lack of consensus and high controversy about the most effective range of motion (ROM) to minimize the risk of injury and maximize the resistance training adaptations. Objective: To conduct a systematic review and meta-analysis of the scientific evidence examining the effects of full and partial ROM resistance training interventions on neuromuscular, functional, and structural adaptations. Methods: The original protocol (CRD42020160976) was prospectively registered in the PROSPERO database. Medline, Scopus, and Web of Science databases were searched to identify relevant articles from the earliest record up to and including August 2020. The RoB 2 and GRADE tools were used to judge the level of bias and quality of evidence. Meta-analyses were performed using robust variance estimation with small-sample corrections. Results: Sixteen studies were finally included in the systematic review and meta-analyses. Full ROM training produced significantly greater adaptations than partial ROM on muscle strength (ES=0.56, P=0.004) and lower-limb hypertrophy (ES=0.88, P=0.027). Furthermore, although not statistically significant, changes in functional performance were maximized by the full ROM training (ES=0.44, P=0.186). Finally, no significant superiority of either ROM was found to produce changes in muscle thickness, pennation angle, and fascicle length (ES=0.28, P=0.226). Conclusion: Full ROM resistance training is more effective than partial ROM to maximize muscle strength and lower-limb muscle hypertrophy. Likewise, functional performance appears to be favored by the use of full ROM exercises. On the other hand, there are no large differences between the full and partial ROM interventions to generate changes in muscle architecture.